Angentine military participation in peace misions. Challenges for defense policy and influence on the organization and functioning of the armed forces - Lafferriere, Guillermo Horacio; Soprano, German Flavio (International Relations, 2016)
This article aims to analyze the Argentine participation in United Nations peacekeeping operations since 1990 to 2013 to determine: 1) regions and countries in which it has been involved; 2) officers deployed profiles; 3) annual total quantitative evolution of military and police involvement; 4) activities carried out by the Argentine Army military personnel; 5) impact of that participation inside the organization, recruitment and training of the personnel of the Army –force that provided the quantitatively most important quotas in the case of the Armed Forces of this country.